Effects of rice husk compost application on soil quality parameters in greenhouse conditions - Zeynep Demir; Coşkun Gülser (Eurasian Journal of Soil Science, 2015)
Effects of rice husk compost (RHC) on some soil quality parameters under greenhouse conditions were investigated. Experiment were conducted in a randomized plot design with different application doses of RHC (0, 3, 6 and 9%) into surface soil (0-20 cm) with three replications in a greenhouse of Agricultural Faculty in Ondokuz Mayıs University. RHC application generally improved the soil quality parameters according to the control treatment during the experiment carried out with growing tomato plant in the greenhouse in 2010. The soil organic matter (OM) contents significantly increased by the application of RHC in the following order; 9%>6%>3%>0%. While RHC applications in the greenhouses significantly reduced pH contents of soils according to the control, the RHC application increased the values of respiration rate (CO2), EC, NO3-N and available phosphorus (P). While the exchangeable Ca values of soils generally decreased, the exchangeable Mg and K values generally increased according to the control with RHC application. Bulk density (BD) values in the greenhouse were reduced with RHC application doses in the following order 0%>3%> 6%>9%. The values of field capacity (FC), permanent wilting point (PWP) and available water capacity (AWC) generally increased according to the control with the application of RHC dosses in the following order 9%>6%>3%. The highest positive correlations among the physical, chemical and biological properties were found between OM and PWP (0.924**), AWC and FC (0.907**), OM and FC (0.897**), CO2 and PWP (0.862**), PWP and FC (0.791**); while the highest negative correlations were found between BD and FC (-0.854**), BD and PWP (-0.871**), BD and OM (-0.868**), BD and CO2 (-0.838**), BD and P (-0.821**), Ca and FC (-0.812**). The highest tomato yield (7.77 ton/da) was obtained with the 9% of RHC application. RHC application to the soil in greenhouse generally improved soil quality and tomato yield.